Human T-bet Governs Innate and Innate-like Adaptive IFN-γ Immunity against Mycobacteria - Yang, Rui; Mele, Federico; Worley, Lisa; Langlais, David; Rosain, Jérémie; Benhsaien, Ibithal; Elarabi, Houda; Croft, Carys A; Doisne, Jean-Marc; Zhang, Peng; Weisshaar, Marc; Jarrossay, David; et al. (Cell, 2020)
Inborn errors of human interferon gamma (IFN-γ) immunity underlie mycobacterial disease. We report a patient with mycobacterial disease due to inherited deficiency of the transcription factor T-bet. The patient has extremely low counts of circulating Mycobacterium-reactive natural killer (NK), invariant NKT (iNKT), mucosal-associated invariant T (MAIT), and Vδ2 γδ T lymphocytes, and of Mycobacterium-non reactive classic T 1 lymphocytes, with the residual populations of these cells also producing abnormally small amounts of IFN-γ. Other lymphocyte subsets develop normally but produce low levels of IFN-γ, with the exception of CD8 αβ T and non-classic CD4 αβ T 1 lymphocytes, which produce IFN-γ normally in response to mycobacterial antigens. Human T-bet deficiency thus underlies mycobacterial disease by preventing the development of innate (NK) and innate-like adaptive lymphocytes (iNKT, MAIT, and Vδ2 γδ T cells) and IFN-γ production by them, with mycobacterium-specific, IFN-γ-producing, purely adaptive CD8 αβ T, and CD4 αβ T 1 cells unable to compensate for this deficit.